The Pattern of Scientific and Islamic Integration:The Implementation of Curriculum Study Program Based International Qualification Framework - Sofyan, Ahmad; Fauzan, Fauzan; Sayuti, Wahdi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
AbstractThe result of this study aims to determine the patterns of scientific and Islamic integration on the curriculum of study programs applying the Indonesian National Qualification Framework, or commonly called KKNI. This study is conducted by using qualitative approach while utilizing document, field observation, and interview as the data collection techniques of this study. Generally, integrated lesson plans with Islamic and Indonesian values in the curriculum of study programs at the Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University in which based on KKNI is still not well-documented. The suitability among ‘graduate profiles’ as the identity of each graduate program was still not proportional directly to the learning achievements or learning outcomes in which has became the reference of the learning implementation. The vision of integration, developed by the university’s stakeholders, has not been well-implemented, either in written documents or in implementation. Nevertheless, in the implementation of learning, most of the study programs, have already integrated the science, Islamic and Indonesian values, both in scientific contexts—for instance, applied in the learning methods, in teaching materials, in the lecture activities—and in the utilization of the Qur’an as one of the sources of lectures.AbstrakHasil penelitian ini bertujuan untuk mengetahui pola integrasi keilmuan dan keislaman pada kurikulum program studi yang menerapkan Kerangka Kualifikasi Nasional Indonesia, atau yang biasa disebut KKNI. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif sambil memanfaatkan dokumen, observasi lapangan, dan wawancara sebagai teknik pengumpulan data penelitian ini. Secara umum, rencana pembelajaran terpadu dengan nilai-nilai Islam dan Indonesia dalam kurikulum program studi di Fakultas Ilmu Pendidikan, Universitas Islam Negeri Syarif Hidayatullah di mana berdasarkan KKNI masih belum terdokumentasi dengan baik. Kesesuaian antara 'profil lulusan' sebagai identitas setiap program pascasarjana masih belum sebanding secara langsung dengan prestasi belajar atau hasil pembelajaran di mana telah menjadi referensi dari pelaksanaan pembelajaran. Visi integrasi, yang dikembangkan oleh para pemangku kepentingan universitas, belum diimplementasikan dengan baik, baik dalam dokumen tertulis atau dalam implementasi. Namun demikian, dalam pelaksanaan pembelajaran, sebagian besar program studi, telah mengintegrasikan nilai-nilai sains, Islam dan Indonesia, baik dalam konteks ilmiah - misalnya, diterapkan dalam metode pembelajaran, bahan ajar, dalam kegiatan kuliah - dan dalam pemanfaatan Alquran sebagai salah satu sumber kuliah. How to Cite : Sofyan, A., Fauzan., Sayuti, W. (2018). The Pattern of Scientific and Islamic Integration:The Implementation of Curriculum Study Program Based International Qualification Framework. TARBIYA: Journal of Education in Muslim Society, 5(2), 212-224. doi:10.15408/tjems.v5i2.11102.